New perspectives on volcano monitoring in a tropical environment: Continuous measurements of soil CO2 flux at Piton de la Fournaise (La Réunion Island, France). Issue 16 (19th August 2017) - Boudoire, G.; Di Muro, A.; Liuzzo, M.; Ferrazzini, V.; Peltier, A.; Gurrieri, S.; Michon, L.; Giudice, G.; Kowalski, P.; Boissier, P.
Abstract: Detecting renewal of volcanic activity is a challenging task and even more difficult in tropical settings. Continuous measurements of soil CO2 flux were carried out at the Piton de la Fournaise volcano during 2013–2016. Since this site is in the tropics, periods of heavy rainfall are in the norm. Measurements covered volcanic unrest after a hiatus of 3.5 years. We find that while temperature has the strongest effect, extreme rainfall causes short‐term noise. When corrected and filtered from the environmental influence, soil CO2 time series permit to detect a major deep magmatic event during March–April 2014, 3 months before the first eruption of the new activity phase. Correlation with geophysical data sets allows timing of further stages of upward fluid ascent. Our study validates soil CO2 flux monitoring in tropical environments as a valuable tool to monitor magma transfer and to enhance understanding of volcano unrest down to the lithospheric mantle. Key Points: Robust correction of environmental influence on time series of soil CO2 flux in tropical environment New procedure for continuous geochemical monitoring and early detection of volcano unrest, including in extreme tropical environment Complementarity between geophysical and geochemical networks to track and study fluid migration from mantle to crustal level